Le mariage forcé au Canada: la criminalisation, une solution ? - Lamboley, Madeline; Jimenez, Estibaliz; Cousineau, Marie-Marthe; Wemmers, Jo-Anne (Criminologie, 2013)
Cet article met en exergue les nombreuses difficultés éprouvées par les femmes victimes de mariage forcé. Celles-ci sont doublement vulnérables du fait, d’une part, des formes d’abus et d’exploitation dont elles peuvent être l’objet et, d’autre part, de leur statut parfois précaire d’immigrantes, en particulier lorsqu’elles sont parrainées par leur conjoint. Des études menées dans certains pays européens, notamment en Norvège et en Belgique, ont mis au jour une situation inattendue, vu l’ampleur que prenait la problématique, signalant une certaine urgence d’agir. Ces pays ont alors fait le choix de criminaliser la pratique des mariages forcés. Le Canada n’a pas pris une telle initiative. À partir d’une étude menée à la fois auprès de femmes vivant, ayant vécu ou étant menacées d’une situation de mariage forcé et d’informateurs clés provenant de divers milieux de pratique oeuvrant auprès d’elles, nous posons la question : la criminalisation est-elle la bonne, voire la seule, solution au problème envisagé ?
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; canada; cours; criminologie; discipline; inégalités; justice sociale; mariage; mariage forcé; montréal; patriarcat; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; violences

Prison sexual abuse: Race, gender, and the rule of law - Buchanan, Kim (Columbia University, 2010)
In this dissertation, I argue that the exemption of prisons from the rule of law fosters abusive institutional practices that reveal the race and gender dynamics of sexual abuse in prison and in the outside world. The first article, Beyond Modesty: Privacy in Prison and the Risk of Sexual Abuse, shows that Fourth Amendment privacy offers little protection against the cross-gender searches and surveillance that expose women prisoners to sexual abuse by male guards. It proposes a reinterpretation of Fourth Amendment privacy that would recognize a constitutional right to be free from the fear, risk and reality of prison sexual abuse. The second article, Impunity: Sexual Abuse in Women's Prisons, shows that an edifice of constitutional, statutory and common-law rules confers near-complete institutional immunity against nearly all prisoner claims of custodial sexual abuse. These immunity rules parallel those of historical status regimes which excluded low-status litigants from courts on the basis of race and gender, such as civil death, slavery, segregation and the common law of marriage and rape--with similar results: low-status women of color are exposed to systematic and institutionalized sexual abuse, and are prevented from seeking protection or redress from the courts. The third article, Our Prisons, Ourselves: Race, Gender and the Rule of Law, develops these insights in men's prisons. In the absence of enforceable external rules, staff and administrators often adopt a gendered practice of institutional governance that requires prisoners to prove their manhood by fighting, and penalizes unmanly men by allowing others to rape them. These unlawful gendered practices are obscured by a false but powerful racialized narrative: most people inside and outside prison believe, inaccurately, that prison rape is mainly black-on-white. By casting sexual violence as a "complex and intractable" race relations problem for which administrators are not to blame, the racial narrative bolsters the rationale for exempting prison administration from the rule of law. Thus the perception (and reality) of unchecked prison violence supplies a reason for courts not to interfere with the unlawful institutional policies that foster it.
Keywords: approches et analyses; criminologie; discipline; droit; genre; intersectionnalité; mémoires/thèses; racisme; ressource en ligne; science politique et droit; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexuelles

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences